Detecção das proteínas p53, p63 e puma no carcinoma de células escamosas corneal de cães: Lucas Bahdour Cossi. - - Cossi, Lucas Bahdour [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Ocular tumors play an increasing concern in veterinary ophthalmology. Corneal squamous cell carcinoma (SCC) is unfrequent in dogs, and by this way it has little studies, and the investigations of carcinogenesis mechanisms are rare. The aim of this work was to identify the p53, p63 and PUMA proteins expression in the spontaneous dog corneal SCC. For this work, were used five cases of corneal SCC and one case of actinic keratitis and their possible contributions to prognosis and therapy. The immunohistochemical analysis could evaluated the number of stained cells by field in optic microscopy using two classifications methods: intensity and immunofrequency. Also, we could evaluated histological grade of tumor related to malignancy in corneal SCC cells by using the mitotic index as a pattern. All samples showed immunolabelling to those proteins studied, although with diversity in intensity and frequency. The authors couldn´t observe relationship between the biggest mitotic index, and, by this way, most malignancy, with the expressions of all analysed proteins. These results could support the conclusions that p53, p63 and PUMA proteins immunoexpression are present in canine corneal SCC and could give help to their carcinogenesis, but they don´t give a prognostic indicator of these tumors
Keywords: Carcinoma de celulas escamosas; Imuno-histoquímica; Cornea; Proteínas; Apoptose; Tumores; Oftalmologia veterinaria; Puma; protein p53